Peningkatan Pemahaman Guru dalam Menulis dan Mempublikasikan Artikel Ilmiah pada Jurnal Online - Rino Richardo; Ahmad Anis Abdullah; Tri Rochmadi; Siti Rohayati; Asrifatun gustini (IKIP PGRI Bojonegoro, 2019)
ABSTRACTThe ability to write scientific articles for teachers is still quite low. While the career development of a teacher, especially in Submitting a Credit Score for promotion, it is very necessary to publish scientific articles as a condition. The writing of this article is part of the implementation of community activities with the aim of increasing teacher understanding in writing and publishing scientific articles carried out in the form of training (workshops). The methods used in this training are lectures, questions and answers, practice to mentoring. The instrument used to measure teachers' understanding abilities related to writing and publication was a pre-test and post-test questionnaire with a Likert scale and was validated. In addition, to measure the level of success of community service activities, an evaluation questionnaire was given to the participants. Based on the results of questionnaire data obtained that the teacher's understanding in writing to submit / publication in online journals increased. Keywords: Writing, Publication, Scientific Articles, Understanding, Teachers ABSTRAKKemampuan dalam menulis artikel ilmiah bagi para guru masih cukup rendah. Sementara pengembangan karir seorang guru terutama dalam Pengajuan Angka Kredit untuk kenaikan golongan sangat diperlukan publikasi artikel ilmiah sebagai salah satu syarat. Tulisan artikel ini merupakan bagian dari pelaksanaan kegiatan masyarakat dengan yang bertujuan untuk meningkatkan pemahaman guru dalam menulis dan mempublikasikan artikel ilmiah yang dilaksanakan dalam bentuk Pelatihan (workshop). Metode yang digunakan dalam pelatihan ini yakni ceramah, tanya jawab, praktek hingga pendampingan. Instrumen yang digunakan untuk mengukur kemampuan pemahaman guru terkait menulis dan publikasi adalah angket pre-test dan post-test dengan skala likert dan telah divalidasi. Selain itu, secara umum untuk mengukur tingkat keberhasilan kegaitan diberikan instrumen angket evaluasi kepada para peserta. Berdasarkan hasil isian data angket diperoleh bahwa pemahaman guru dalam menulis hingga mensubmit/publikasi pada jurnal online meningkat. Kata Kunci: Menulis, Publikasi, Artikel Ilmiah, Pemahaman, Guru